Incentives for conservation in Tigray, Ethiopia: Findings from a household survey - Fitsum Hagos; Stein Terje Holden (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2017)
Understanding the problem of land degradation in a given spatial and temporal context, requires looking at the community baseline conditions such as the natural resource base, human resources, existing institutions and infrastructure base, and how these conditions interact with policies and institutions to influence human responses and thereby affect productivity, livelihood security and the natural resource base. This study provides a description of the land users' priorities, attitudes and perceptions, household characteristics and socio-economic status, access to credit, and farm inputs, tenurial arrangements and variations in land quality and technology characteristics and their effects on the households' interest in and ability to invest in conservation technologies based on a preliminary statistical analysis from a survey of 400 households in 16 communities carried out in 1998. Furthermore, it poses important questions that could serve as basis for further rigorous econometric analysis and future research endeavor.
Keywords: 330